THE EFFECT OF PERORAL POLYVINYL CHLORIDE MICROPLASTIC ON THE VALUE OF PROTHROMBIN TIME AND ACTIVATED PARTIAL THROMBOPLASTIN TIME IN RATTUS NORVEGICUS WISTAR STRAIN - David Karunia Jaya; Yudhiakuari Sincihu; Niluh Suwasanti (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Introduction: Microplastics can enter the human digestive system as polyvinyl chloride (PVC). Microplastics ingested by humans will accumulate in several organs. Microplastic accumulation in the liver causes inflammation, which damages hepatocyte cells, impairing liver synthesis function, one of which is the synthesis of blood clotting factors.Purpose: The purpose of this study was to determine the effect of oral microplastic polyvinyl chloride on prothrombin time (PT) and activated partial thromboplastin time (APTT) in Rattus norvegicus strain Wistar (APTT).Method: The experimental design incorporated a post-test-only control group. There were 12 rats randomly assigned to the control (K) or experimental (E) groups. For 28 days, Group E was exposed to microplastic type PVC at a concentration of up to 0.5 mg/day in 1 cc of Aquabidest via an oral probe. Blood samples were analyzed using a coagulation analyzer at BBLK Surabaya. The statistical test used an independent t-test.Result: There was a significant difference in the mean PT value of group K (9.8 ± 0.99 seconds) compared to group E (14.23 ± 9 seconds) (p=0.024) and the mean APTT value of group K(18.32 ± 7.96 seconds) compared to group E(26.1 ± 18.15 seconds) (p=0.022).Discussion: These findings confirm the theory that exposure to polyvinyl chloride microplastics in the liver can induce hepatocyte cell inflammation and impair the liver's ability to synthesize blood clotting factors, resulting in prolonged PT and APTT values.Conclusion: Oral administration of PVC microplastic affects PT and APTT values.